Pengaruh Berbagai Jenis Media Tanam Organik Dan Dosis Ab Mix Pada Budidaya Hidroponik Sistem Wick Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Keriting (Brassica juncea l.) Varietas Samhong King - Laili, Ulfi Zulfa; Syah, Bastaman; Rahayu, Yayu Sri (JURNAL AGROPLASMA, 2023)
Hydroponic system is a system of agricultural cultivation using water containing nutrients for plant growth, hydroponics can be done on a narrow land or in the yard. This study aims to obtain the type of planting media and the type of AB Mix dosage that gives the highest results on the growth and yield of Curly Mustard (Brassica juncea l.) Samhong King variety in the hydroponic wick system. This experiment was conducted in the greenhouse of Taiwan Technical Mission at Tanjungpura Ring Road, Karangpawitan, West Karawang District, Karawang Regency, West Java Province, from February to April 2023.The research method used was experimental method using factorial Randomized Group Design (RAK). There are 2 factors consisting of 16 treatments. The first factor is the type of planting media consisting of 4 levels, namely M0 (Rockwool), M1 (Cocofiber), M2 (Sawdust) and M3 (Husk Charcoal). The second factor is the type of AB Mix dosage which consists of 4 levels, namely D0 (1000 ppm), D1 (1100 ppm), D2 (1200 ppm) and D3 (1300 ppm). Each experiment was repeated 3 times so that a total of 48 experimental units were obtained. The results showed that there was an interaction effect between the type of planting media and the type of AB Mix dosage on the number of leaves at the age of 28 hst on curly mustard greens (Brassica juncea L.) Samhong King variety in the hydroponic wick system. At the level of planting media m1 cocofiber, the optimal type of fertilizer is a dose of AB Mix d3 1300 ppm with a fresh weight of 153.59 g. It gives the highest yield on planting media m1 cocofiber with a yield of 186.87 g. The highest yield is at the level of planting media m1 cocofiber.